Ketamine's Effects on the Glutamatergic and GABAergic Systems: A Proteomics and Metabolomics Study in Mice - Weckmann, Katja (Mol Neuropsychiatry, 2019)
Ketamine, a noncompetitive, voltage-dependent N-Methyl-D-aspartate receptor (NMDAR) antagonist, has been shown to have a rapid antidepressant effect and is used for patients experiencing treatment-resistant depression. We carried out a time-dependent targeted mass spectrometry-based metabolomics profiling analysis combined with a quantitative based on in vivo (15)N metabolic labeling proteome comparison of ketamine- and vehicle-treated mice. The metabolomics and proteomics datasets were used to further elucidate ketamine's mode of action on the gamma-aminobutyric acid (GABA)ergic and glutamatergic systems. In addition, myelin basic protein levels were analyzed by Western Blot. We found altered GABA, glutamate and glutamine metabolite levels and ratios as well as increased levels of putrescine and serine – 2 positive modulators of the NMDAR. In addition, GABA receptor (GABAR) protein levels were reduced, whereas the alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) subunit Gria2 protein levels were increased upon ketamine treatment. The significantly altered metabolite and protein levels further significantly correlated with the antidepressant-like behavior, which was assessed using the forced swim test. In conclusion and in line with previous research, our data indicate that ketamine impacts the AMPAR subunit Gria2 and results in decreased GABAergic inhibitory neurotransmission leading to increased excitatory neuronal activity.